How to "Start Small and Just Keep Moving Forward": Mixed Methods Results From a Stepped-Wedge Trial to Support Evidence-Based Processes in Local Health Departments - Rebekah R. Jacob; Renee G. Parks; Peg Allen; Stephanie Mazzucca; Yan Yan; Sarah Kang; Debra Dekker; Ross C. Brownson; Ross C. Brownson (Frontiers Media S.A., 2022)
BackgroundLocal health departments (LHDs) in the United States are charged with preventing disease and promoting health in their respective communities. Understanding and addressing what supports LHD's need to foster a climate and culture supportive of evidence-based decision making (EBDM) processes can enhance delivery of effective practices and services.MethodsWe employed a stepped-wedge trial design to test staggered delivery of implementation supports in 12 LHDs (Missouri, USA) to expand capacity for EBDM processes. The intervention was an in-person training in EBDM and continued support by the research team over 24 months (March 2018-February 2020). We used a mixed-methods approach to evaluate: (1) individuals' EBDM skills, (2) organizational supports for EBDM, and (3) administered evidence-based interventions. LHD staff completed a quantitative survey at 4 time points measuring their EBDM skills, organizational supports, and evidence-based interventions. We selected 4 LHDs with high contact and engagement during the intervention period to interview staff (n = 17) about facilitators and barriers to EBDM. We used mixed-effects linear regression to examine quantitative survey outcomes. Interviews were transcribed verbatim and coded through a dual independent process.ResultsOverall, 519 LHD staff were eligible and invited to complete quantitative surveys during control periods and 593 during intervention (365 unique individuals). A total of 434 completed during control and 492 during intervention (83.6 and 83.0% response, respectively). In both trial modes, half the participants had at least a master's degree (49.7-51.7%) and most were female (82.1-83.8%). No significant intervention effects were found in EBDM skills or in implementing evidence-based interventions. Two organizational supports scores decreased in intervention vs. control periods: awareness (−0.14, 95% CI −0.26 to −0.01, p < 0.05) and climate cultivation (−0.14, 95% CI −0.27 to −0.02, p < 0.05) but improved over time among all participants. Interviewees noted staff turnover, limited time, resources and momentum as challenges to continue EBDM work. Setting expectations, programmatic reviews, and pre-existing practices were seen as facilitators.ConclusionsChallenges (e.g., turnover, resources) may disrupt LHDs' abilities to fully embed organizational processes which support EBDM. This study and related literature provides understanding on how best to support LHDs in building capacity to use and sustain evidence-based practices.